1999
DOI: 10.7326/0003-4819-130-6-199903160-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of Three Approaches to the Diagnosis of Sleep Apnea: Polysomnography, Home Testing, and Empirical Therapy

Abstract: The cost-utility of polysomnography instead of home study or no testing in the diagnosis of OSAS compares favorably with that of other procedures for which society judges the added utility per dollar spent to be worthwhile. More precise determination of certain key variables in this model should be a goal of future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 20 publications
1
74
1
Order By: Relevance
“…Economic analyses have compared the cost-effectiveness of management pathways that incorporate diagnostic strategies using HSAT or PSG. [112][113][114] All have concluded that PSG is the preferred diagnostic strategy from an economic perspective for adults suspected to have moderate to severe OSA. An important factor in these analyses is the favorable cost-effectiveness of OSA treatment in patients with moderate to severe OSA, particularly when longer time horizons are considered.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Economic analyses have compared the cost-effectiveness of management pathways that incorporate diagnostic strategies using HSAT or PSG. [112][113][114] All have concluded that PSG is the preferred diagnostic strategy from an economic perspective for adults suspected to have moderate to severe OSA. An important factor in these analyses is the favorable cost-effectiveness of OSA treatment in patients with moderate to severe OSA, particularly when longer time horizons are considered.…”
Section: Quality Of Lifementioning
confidence: 99%
“…We compare our results to those of Chervin et al (40), who conducted a cost-utility analysis of polysomnography, not testing at all, and home diagnostic testing using portable monitors in a hypothetical cohort of patients suspected of having OSAS, presumably such as those referred to a sleep center. Treatment was offered not only to the subset with confirmed OSAS on home study or polysomnography, but to everyone in the "no-testing" group.…”
Section: Discussionmentioning
confidence: 62%
“…Given the paucity of data regarding longer-term health outcomes and costs, our analysis assessed costs of diagnosis and treatment of sleep apnea which occur within the first year, when these costs are presumably the highest (40). One study has addressed this issue in a more general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been only a few randomized clinical trials involving different strategies for the diagnosis and treatment of OSAS that include the collection of data about quality of life, health, and economic aspects. (57)(58)(59)(60) One review, (57) using a model for the cost-utility analysis, comparing laboratory polysomnography, in-home monitoring, and no testing for five years after the initial evaluation for OSAS, including CPAP therapy, involved a hypothetical cohort of individuals suspected of having OSAS. Quality of life, survival, and charges for (as proxies for costs of) each diagnostic method were considered.…”
Section: Cost-effectiveness Of the Use Of Pmdsmentioning
confidence: 99%